How to Build Your Brand : Implementing a Proven and Effective Process. - Lubin, Laurence (Productivity Press, 2022)
Brand Strategy is the most important marketing talent. A 2020 Gartner Survey of 400 CMO's cited Brand Strategy as the most needed skill, more valuable than analytics, UX, digital commerce. Previous books on the subject analyze the qualities and characteristics of well-regarded brands. What these books don't offer are the "how to's" of branding. This book empowers readers by teaching them the author's unique, time-tested Success Model, and step-by-step, repeatable method for successful brand building. After reading this insightful book, you will learn how to: Develop "big picture" insight that inspires big brand ideas Use imagery to understand the fundamental human values that give our life meaning as well as learn about the feelings that reveal our hopes and dreams. Develop highly motivating brand concepts that link to our values and aspirations. Create the tactical roadmap to implement the concepts. The author clearly shares the: Success Model that defines the world's most successful brands. Case studies that demonstrate the Model in action. Step-by-step method to implement the model. The evidence -- scientific and psychological --.that supports the model and method. Essentially, this book empowers readers to become skilled brand builders enabling them to succeed personally, socially, and professionally